2015
DOI: 10.3390/ijerph121114887
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposure and Physical Activity in China: Current Knowledge, Public Health Implications, and Future Research Needs

Abstract: Deteriorating air quality in China has created global public health concerns in regard to health and health-related behaviors. Although emerging environmental regulations address ambient air pollution in China, the level of enforcement and long-term impact of these measures remain unknown. Exposure to air pollution has been shown to lead to multiple adverse health outcomes, including increased rates of heart disease and mortality. However, a lesser-known but increasingly significant concern is the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…3 Therefore, there is increasing concern about the trade-off between the health benefits of physical activity and potential health hazards from increased air pollution exposures. 26 We observed a greater association between PM 2.5 and stroke for high levels of physical activity. A few exposure studies also found reduced lung function associated with exercises in highly polluted areas.…”
Section: Discussionmentioning
confidence: 49%
“…3 Therefore, there is increasing concern about the trade-off between the health benefits of physical activity and potential health hazards from increased air pollution exposures. 26 We observed a greater association between PM 2.5 and stroke for high levels of physical activity. A few exposure studies also found reduced lung function associated with exercises in highly polluted areas.…”
Section: Discussionmentioning
confidence: 49%
“…Outdoor physical activity is already a culturally rooted daily lifestyle for Chinese people [12]. Regular exercise has been shown to improve overall health and wellbeing, while physical inactivity is the fourth leading risk for global mortality, contributing to 3.2 million deaths annually [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Warmer temperatures and extreme weather events reduce agricultural production and also directly affect human health through various diseases, such as heat-related disorders, mental health problems, vector-borne diseases, food-borne and water-borne diseases, and respiratory and allergic disorders (12). Relevant environmental regulations and laws have not yet solved air pollution in China, and the long-term effects of these measures remain obscure (13). …”
Section: Health Problems In Chinamentioning
confidence: 99%
“…According to the WHO, 16 of the 20 worst polluted cities worldwide are located in China. The negative impact of this serious pollution situation in China is the same or still worse than that of the SARS epidemic in 2003 (13), which in turn may increase the risk of health problems in the populace, including cardiovascular and cerebrovascular diseases (19, 20). …”
Section: Health Problems In Chinamentioning
confidence: 99%
See 1 more Smart Citation